Multirate Universal Radar Target Simulator for an Accurate Moving Target Simulation - Körner, Georg; Hoffmann, Marcel; Neidhardt, Steffen; Beer, Matthias; Carlowitz, Christian; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2021)
This article presents a new universal radar target simulator (RTS) principle based on multirate sampling. The proposed concept enables a realistic emulation of moving targets independently of the radar type and signal and is suited for all common modulation types, such as frequency-modulated continuous-wave (FMCW), chirp sequence (CS), orthogonal frequency division multiplexing (OFDM), and pseudorandom impulse sequences. This versatile applicability is achieved by delaying the radar signal with a time-variant delay that is changed continuously over time. Analog systems use mixing to simulate moving targets, which is not precise. Standard digital radio frequency memory (DRFM) systems with discrete programmable time delays, in contrast, typically drop or delay samples to simulate moving targets. This time-delay discretization, however, introduces discontinuities to waveforms and therefore creates spurious signals. These distortions particularly affect processing in the Doppler dimension. To overcome this disadvantage, the proposed multirate system simulates continuous target movement and the Doppler effect of real targets by using different sample rates for an analog-to-digital converter (ADC) and digital-to-analog converter (DAC). The resulting Doppler phase variation equals that of a real moving target exactly. With this multirate RTS, even slow-moving real-world targets can be mimicked accurately. The attractive properties of the proposed RTS concept are verified by real-world measurements with a 77-GHz demonstration syste